Effectiveness of Nursing Caring Behavior to The Satisfaction of Hospital Patients in Puskesmas Wotu - Yudi Adnan (Afiasi : Jurnal Kesehatan Masyarakat, 2020)
Caring is an attention and action towards others (patients) to provide assistance, support, respect and empathy in providing physical care to avoid a unexpected condition supported by sources of knowledge, patience, and hope. Nurse caring behaviour will be very important in influencing service quality and client satisfaction. The purpose of this study was to analyze nurse caring behaviour in increasing the satisfaction of inpatients at the Puskesmas Wotu. The design of this study is a correlative study. The population were 87 respondents with a purposive sampling technique in which all population amounts were used as research samples. The results of a statistical study using the spearmen test, it was found that r value=0.529. That is, the level of strength of the relationship between strong variables. The relationship between these two variables is unidirectional, thus it can be interpreted that the quality of caring care increases the satisfaction of inpatients will also increase. Furthermore, there is a significant relationship between Nurse behavior variables with the Patients Satisfaction (Sig.=0,000). Nurse caring behavior needs to be increased again with training and making standard guidelines.